Development of novel Escherichia coli cell-based biosensors to monitor Mn(II) in environmental systems - Jeon, Yangwon; Lee, Yejin; Kim, Yeonhong; Park, Chanhee; Choi, Hoon; Jang, Geupil; Yoon, Youngdae (Frontiers in Microbiology, 2022)
Escherichia coli uses manganese (Mn(II)) as an essential trace element; thus, it has a genetic system that regulates cellular Mn(II) levels. Several genes in the mnt-operon of E. coli respond to intercellular Mn(II) levels, and transcription is regulated by a transcription factor (MntR) that interacts with Mn(II). This study aimed to develop Mn(II)-sensing biosensors based on mnt-operon genetic systems. Additionally, the properties of biosensors developed based on the promoter regions of mntS, mntH, and mntP were investigated. MntR represses the transcription of MntS and MntH after binding with Mn(II), while it induces MntP transcription. Thus, Mn(II) biosensors that decrease and increase signals could be obtained by fusing the promoter regions of mntS/mntH and mntP, with egfp encoding an enhanced green fluorescent protein. However, only the biosensor-based mntS::egfp responded to Mn(II) exposure. Further, E. coli harboring PmntS::egfp showed a concentration-dependent decrease in fluorescence signals. To enhance the sensitivity of the biosensor toward Mn(II), E. coli containing a deleted MntP gene that encodes Mn(II) exporter, was used as a host cell for biosensor development. The sensitivity toward Mn(II) increased by two times on using E. coli-mntP, and the biosensor could quantify 0.01–10 μM of Mn(II). Further, the applicability of Mn(II) in artificially contaminated water samples was quantified and showed >95% accuracy. The newly developed Mn(II) biosensors could detect and quantify the residual Mn(II) from mancozeb in soil samples, with the quantification accuracy being approximately 90%. To the best of our knowledge, this is the first Mn (II)-specific bacterial cell-based biosensor that serves as a valuable tool for monitoring and assessing the risks of Mn(II) in environmental systems.